Find detailed and accurate answers to your questions on IDNLearn.com. Our platform provides trustworthy answers to help you make informed decisions quickly and easily.
Sagot :
Answer:
Consider the following identity:
- a³ - b³ = (a + b)(a² - ab + b²)
Let a = 2, b = 1/2
- (2 + 1/2)(2² - 2*1/2 + 1/2²) =
- 2³ - (1/2)³ =
- 8 - 1/8
Use the algebraic identity given below
[tex]\boxed{\sf a^3-b^3=(a+b)(a^2-ab+b^2)}[/tex]
[tex]\\ \sf\longmapsto (2+\dfrac{1}{2})(2^2-1+\dfrac{1}{4})[/tex]
[tex]\\ \sf\longmapsto (2+\dfrac{1}{2})(2^2-2\times \dfrac{1}{2}+\dfrac{1}{2}^2)[/tex]
- Here a =2 and b=1/2
[tex]\\ \sf\longmapsto 2^3-\dfrac{1}{2}^3[/tex]
[tex]\\ \sf\longmapsto 8-\dfrac{1}{8}[/tex]
Your participation means a lot to us. Keep sharing information and solutions. This community grows thanks to the amazing contributions from members like you. Thank you for visiting IDNLearn.com. We’re here to provide dependable answers, so visit us again soon.